A prospective audit of preprocedural fasting practices on a transplant ward: when fasting becomes starving. Issue 5 (13th January 2016) - Vidot, Helen; Teevan, Kate; Carey, Sharon; Strasser, Simone; Shackel, Nicholas
Abstract : Aims and objectives: To investigate the prevalence and duration of preprocedural medically ordered fasting during a period of hospitalisation in an Australian population of patients with hepatic cirrhosis or following liver transplantation and to identify potential solutions to reduce fasting times. Background: Protein‐energy malnutrition is a common finding in patients with hepatic cirrhosis and can impact significantly on survival and quality of life. Protein and energy requirements in patients with cirrhosis are higher than those of healthy individuals. A significant feature of cirrhosis is the induction of starvation metabolism following seven to eight hours of food deprivation. Many investigative and interventional procedures for patients with cirrhosis necessitate a period of fasting to comply with anaesthesia guidelines. Design: An observational study of the fasting episodes for 34 hospitalised patients with hepatic cirrhosis or following liver transplantation. Methods: Nutritional status was estimated using subjective global assessment and handgrip strength. The prevalence and duration of fasting practices for diagnostic or investigational procedures were estimated using electronic records and patient notes. Results: Thirty‐three patients (97%) were malnourished. Twenty‐two patients (65%) were fasted during the observation period. There were 43 occasions of fasting with a median fasting time of 13·5 hours. On 40 occasions fasting times exceeded the maximum six‐hour guideline recommended prior to the administration of anaesthesia by the majority of Anaesthesiology Societies. The majority of procedures (77%) requiring fasting occurred after midday. Eating breakfast on the day of the procedure reduced fasting time by 45%. Conclusions: Medically ordered preprocedural fasting times almost always exceed existing guidelines in this nutritionally compromised group. Relevance to clinical practice: Adherence to fasting guidelines and eating breakfast before the procedure can reduce fasting times significantly and avoid the potential induction of starvation metabolism in this nutritionally at risk group.